Logico-Empirisme Paradigma Positivisme Logis: Kritik Dan Tawaran Epistemologi Alternatif - Nugraha, Harry Setya; Satria, Indah; Prihandini, Yudiana Dewi (Jurnal Hukum IUS QUIA IUSTUM, 2025)
Logico-empiricism emphasises the importance of empirical verification as a scientific criterion for distinguishing meaningful from meaningless statements. Although logico-empiricism has made significant contributions to the development of the philosophy of science and has been practically beneficial for every legal scholar, criticisms of the a variety of assumptions underlying logico-empiricism have emerged from several perspectives. Therefore, this article is important to write in order to: 1) explain and deepen the criticisms of logico-empiricism assumptions by focusing on the perspective of dogmatic legal science; 2) offer an alternative epistemology to address these criticisms. This study uses a conceptual approach supported by secondary data sources. The results show that there are six criticisms of the logico-empiricism assumptions of the logical positivism paradigm when viewed from the perspective of dogmatic legal science. These criticisms highlight the tendency of logico-empiricism to reduce legal complexity, limit the scope of explanation, generalise inappropriately, raise questions of objectivity, and ignore social, political, and societal dynamics in the formation and application of law. This critique also demonstrates the limitations of the logico-empiricist approach, necessitating a more inclusive and interdisciplinary alternative epistemology. Several alternative epistemologies proposed to address criticisms of logico-empiricism include hermeneutics, pragmatism, phenomenology, and falsificationism. It is also possible to integrate these various approaches to form a complementary methodological framework, which the author calls "critical-pragmatic hermeneutic phenomenology." This approach is advantageous because it is holistic, open to revision, contextual, practically useful, and respectful of human experience.